Avoiding vascular complications in insular glioma surgery – A microsurgical anatomy study and critical reflections regarding intraoperative findings - Isolan, Gustavo Rassier; Buffon, Viviane; Maldonado, Igor; Monteiro, Jander Moreira; Yağmurlu, Kaan; Ribas, Carmen Austrália Paredes Marcondes; Roesler, Rafael; Malafaia, Osvaldo (Frontiers in Surgery, 2022)
INTRODUCTION: Vascular lesions in insular glioma surgery can severely impact patients' quality of life. This study aims to present the results of our dissections and authors’ reflections on the insular vascular anatomy. MATHERIALS AND METHODS: The insular vascularization was examined using ×3 to ×40 magnification in 20 cadaveric cerebral hemispheres in which the arteries and veins had been perfused with colored silicone. RESULTS: In insular gliomas, this individualization of the anatomical structures is rarely possible, as the gyri are swollen by the tumor and lose their individuality. In the transsylvian approaches, the anatomical parameters for delimiting the insula in tumors are best provided by the superior and inferior circular sulci. The branches of the MCA are easily identified in the transcortical approach, but only at the end of the surgery after the tumor is resected. ). One of the factors under-discussed in the literature is the involvement of the lenticulostriate arteries by the medial part of the tumor. In our experience of 52 patients (article submitted to publishing), LSTa were founded to be involved by the tumor in 13 cases. In 39 patients, there was no involvement of the LSTa, which allowed a more aggressive resection. Early preoperative identification of the anterior perforated substance on the MRI and its proximity to the tumor may help determine the route of the LSTa over the medial tumor boundaries. DISCUSSION: Our reflections introduced our imaging and anatomical concept regarding LSTa in insular glioma surgery. Accurate identification of origin, route, and distribution of the LSTa is pivotal to surgical success, especially in the lateral group. The anatomical knowledge of their path directly impacts the extent of tumor resection and functional preservation. CONCLUSION: Knowledge of microsurgical anatomy, brain mapping, and surgical experience counts a lot in this type of surgery, creating a reasonable procedure flowchart to be taken intraoperatively.